Electronic Nicotine Product (ENP) Graphic Warnings: Association between Electronic Nicotine Product (ENP) Graphic Warnings: Association between Exposure and Changes in Perceived Susceptibility and Severity of Explosion and Exposure and Changes in Perceived Susceptibility and Severity of Explosion and Lung Injuries - Matthew E. Rossheim; Xiaoquan Zhao; Christian Seiter; Ogechi Emechebe; Eric Soule (New Prairie Press, 2024)
Electronic nicotine products (ENPs) are the most prevalent form of tobacco use among U.S. young adults. Research is needed to investigate how to communicate new risks from ENPs to the public. In this study, we tested the comparative persuasiveness of ENP explosion and lung injury graphic warnings. We recruited a sample of 343 young adults (18 to 28 years; 146 male, 197 female), including both ENP users and nonusers, via Amazon Mechanical Turk in October 2020. We randomly assigned participants to one of six exposure conditions: two images of lung injuries with prevalence statistics, two images of battery explosion injuries with prevalence statistics, and two images of ENPs with messages about chemicals or nicotine/addiction. We measured perceptions and intention to use ENPs before and after exposure. Linear regression models examined whether exposure conditions were associated with post-exposure perceived susceptibility and severity of ENP lung injuries and explosion injuries, perceived intensity, fear, and intention to use, adjusting for baseline values and potential confounders. Compared to the chemicals/nicotine messages, explosion and lung injury stimuli were perceived to be more intense (p < .001) and evoked greater fear (p < .001). Both explosion injury images were associated with increased perceived susceptibility (p < .01) and severity (p < .001). One lung injury image was associated with increased perceived susceptibility (p < .01) and reduced intention to use ENPs (p < .05). Our results show that ENP graphic warnings can increase threat perceptions about ENP lung and explosion injuries among young adults. Similar graphic warnings may be effective for other harms associated with ENPs.